Cytopathology in the Diagnosis of Oral Trichomoniasis in a Rock Pigeon (Columba livia) - Arenales, Alexandre; Almeida, Ana Carolina Ortegal; Prado, Luiz Fernando; Garcia, Sérgio; Luvizotto, Maria Cecília Rui (Brazilian Journal of Veterinary Pathology, 2014)
A Rock Pigeon (Columba livia) submitted for necropsy had an oral white-yellow mass with a friable surface and putrid odor. Impression smears were performed and tissue samples were collected for histopathology. Cytopathological analysis revealed numerous pyriform protozoa, compatible with Trichomonas gallinae. Protozoans were not evident within the lesions by histopathology after staining the samples with Hematoxylin and Eosin or Gomori methenamine silver (GMS) stain. We conclude that impression smears from avian oral trichomoniasis suspects, even during post-mortem evaluation, can be a useful technique for the diagnosis of this disease.